The production of knowledge as a tool to change the know and do in the Brazilian nursing - Jorge, Maria Salete Bessa (Rev Rene, 2007)
The Journal of the Nordeste RENE Nursing Network enables the dissemination of knowledge, both in nursing and other areas of scientific knowledge, socializing nursing research for the whole country, given that in addition to the Portal VHL Nursing, the journal encontra- now in CINAHL, a fact that shows the magazine's growth in the national and international levels.